Memahami Makna-Makna Simbolik Pada Upacara Adat Sedekah Laut di Desa Tanjungan Kecamatan Kragan Kabupaten Rembang - Abdurrohman, Muhammad (Jurnal The Messenger, 2015)
This study aims to determine the meanings contained in the sequence of the ceremonial procession in the village of Sea Alms Tanjungan as an annual tradition organized by the local community. Theory basis used is the symbol by Susanne Langer's theory which states that a symbol or set of symbols works by connecting a concept, the general idea, pattern, or shape. Symbols are human conceptualization of a thing, there is a symbol for something. Research methods in use is descriptive qualitative, by describing the results that have been obtained from observation and depth interviews with informants. Results in the can that is symbolic ceremonies Sea Alms is a form of implementation of gratitude local community to God Almighty for the gift that has been given, as well as their respect to guard the sea are believed during this important role for the safety of the villagers Tanjungan. This research linkages with communication studies is that people can establish a value of life by applying them in the form of symbols that can be agreed upon by the perpetrators so as to form a culture.